Perancangan Alat Bantu Ergonomis Pada Proses Produksi Agar-Agar - Yusuf Mauluddin; Dewi Rahmawati; Ichsan Faturachman (Institut Teknologi Garut, 2023)
Poor working posture can cause a number of problems in the workplace which can result in accidental losses for employees. One of the consequences that can arise from these activities is musculoskeletal complaints. The aim of this research is to determine the body positions used when working in the jelly making process which can cause injuries based on complaints from production operators. The research data used is the mix method and NBM questionnaire method, RULA and REBA methods to identify musculoskeletal complaints among operators to ascertain the level of body posture hazards and the EFD method to design ergonomic assistive devices. The results of the research obtained from the NBM questionnaire from 9 operators revealed that the most common complaint was pain in the left forearm, which was 11% of all complaints and 67% of them were very painful. The REBA method for mixing raw materials gets a level-2 action rating, while RULA for packaging activities gets a level-3 action rating. The highest level of activity in the packaging area is the basis for creating ergonomic tools.